Epistemologi Tafsir al-Jami' li Ahkam al-Qur'an Karya al-Qurtubi - abidin, ahmad zainal; Zulfikar, Eko (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
A review of epistemology of al-Qurtubi tafsir is very important. This is to determine how the origins, sources, methods, and steps are taken by the author. As comprehensive tafsir with fiqh pattern, this work contributes information and relatively different approach in which the author is far from fanaticism sect. He uses various arguments of the scholars then he chooses a strong one according to the mufassir. With descriptive-analytic study, this paper finds that al-Qurtubi epistemology base is a combination of bil ma'sur and bil ma'qul, a combination of textual and contextual which expresses many perspectives before it has been chosen as the truth by al-Qurtubi without fanaticism impression against embraced sect. Based on the review of his resume, this paper proves that the interpretation of al-Qurtubi is a representation in which the author associates and responds to the problems that happened at that era and answers based on the era.